ANALISIS COST VOLUME PROFIT DENGAN ACTIVITY BASED COSTING UNTUK MERENCANAKAN LABA - DAMAYANTI, FITRI (Jurnal Akuntansi AKUNESA, 2016)
AbstractThis research aims to determine the profit planning with Cost Volume Profit analysis with Activity Based Costing approach as profit planning tool hospital. This research was conducted at hospital because it has not implemented the Cost Volume Profit analysis as a tool to plan for profit. Data analysis was performed using descriptive qualitative. The results showed that the Cost Volume Profit with the approach of Activity Based Costing is the right way in Planning earnings for the implementation is done by tracking and classifying sales data and costs based on the behavior of costs, mengkalisifikasian activity-based costing, analyzing CVP with ABC approach, CVP analysis using the break even point, margin of safety, DOL, stipulate various alternatives used to achieve profit targets and analyze alternatives used by using analysis CVP.Kata Kunci : Cost Volume Profit, Activity Based Costing, Profit